Affinity‐Driven Covalent Modulator of the Glyceraldehyde‐3‐Phosphate Dehydrogenase (GAPDH) Cascade. (14th May 2018) - Chern, Jeffy; Lu, Chun‐Ping; Fang, Zhanxiong; Chang, Ching‐Ming; Hua, Kuo‐Feng; Chen, Yi‐Ting; Ng, Cheng Yang; Chen, Yi‐Lin Sophia; Lam, Yulin; Wu, Shih‐Hsiung
Abstract: Traditional medicines provide a fertile ground to explore potent lead compounds, yet their transformation into modern drugs is fraught with challenges in deciphering the target that is mechanistically valid for its biological activity. Herein we reveal that ( Z )‐(+)‐isochaihulactone (1 ) exhibited significant inhibition against multiple‐drug‐resistant (MDR) cancer cell lines and mice xenografts. NMR spectroscopy showed that1 resisted an off‐target thiolate, thus indicating that1 was a target covalent inhibitor (TCI). By identifying the pharmacophore of1 (α, β‐unsaturated moiety), a probe derived from1 was designed and synthesized for TCI‐oriented activity‐based proteome profiling. By MS/MS and computer‐guided molecular biology approaches, an affinity‐driven Michael addition of the noncatalytic C247 residue of GAPDH was found to control the "ON/OFF" switch of apoptosis through non‐canonically nuclear GAPDH translocation, which bypasses the common apoptosis‐resistant route of MDR cancers.